Kajian Penerapan Bimbingan Kelompok untuk Meningkatkan Motivasi dan Proses Belajar Siswa - Grania Indri Wahyuni; Afriani Daun Langi; Filadelfia Franandas; Novrianti T Mindi; Marlina Limbong (Pengharapan : Jurnal Pendidikan dan Pemuridan Kristen dan Katolik, 2026)
This study aims to examine the application of group guidance in improving students' learning processes at the secondary school level. Group guidance is one of the services in guidance and counseling that allows students to discuss, share experiences, and develop problem-solving skills in a group setting. The background of this research stems from the observation that many students experience difficulties in their learning process, including low motivation, ineffective learning strategies, and an inability to manage academic pressure. The method used in this study is a literature review approach that examines various relevant research and theories. The results show that group guidance has a significant positive impact on improving students' learning processes, including increasing learning motivation, developing effective study habits, enhancing social interaction among students, and reducing academic anxiety. Group guidance also provides a safe space for students to express their academic difficulties and receive constructive support from peers and counselors. The implications of this research suggest that group guidance services need to be consistently and systematically implemented in schools as part of a comprehensive guidance and counseling program. Schools are recommended to design structured group guidance programs with clear objectives and methods tailored to students' developmental needs. This approach is proven to be effective in supporting students' academic achievement and personal development.